QTLs CONTROLLING SEED WEIGHT AND DAYS TO FLOWERING IN MUNGBEAN [Vigna radiata (L.) Wilczek], THEIR CONSERVATION IN AZUKI BEAN [V. angularis (Ohwi) Ohwi & Ohashi] AND RICE BEAN [V. umbellata (Thunb.) Ohwi & Ohashi] - Somta, Prakit; Chankaew, Sompong; Kongjaimun, Alisa; Srinives, Peerasak (AGRIVITA, Journal of Agricultural Science, 2015)
Mungbean (Vigna radiata (L.) Wilczek) is a socio-economically important legume crop of Asia. Varieties with large seed size and early maturity are preferred in commercial production. In this study, we identified quantitative trait loci (QTL) controlling seed weight and days to flowering in mungbean. The mapping population comprises 155 F2-derived lines from a cross between Kamphaeng Saen 1 (large-seeded and early flowering) and V4718 (small-seeded and late flowering). The F2 population was analyzed with 67 simple sequence repeat markers. The F2:3 families were evaluated for 100-seed weigh and days to flowering in two years, 2008 (one season) and 2011 (two seasons). Composite interval mapping identified six QTLs for 100-seed weight and 5 QTLs for days to flowering. Three genomic regions harbored QTLs for both seed weight and days to flowering, revealing association between the two traits. Comparison of QTLs for both traits found in this study with those reported in azuki bean (Vigna angularis (Willd.) Ohwi & Ohashi) and rice bean (Vigna umbellata (Thunb.) Ohwi & Ohashi) revealed that several QTLs are conserved among the three Vigna species.Â